Kali Linux: análise teórica do seu emprego na segurança da informação - OLIVEIRA, Mácio Leandro Mota de (2024)
The constant technological evolution brought about by the microcomputing revolution and the advent of the internet has allowed for significant advancements in social relations, production, and human communications. However, despite its countless benefits, this technological progress also brings new forms of threats, making data that is as important as it is confidential vulnerable. Thus, the field of Computer Science in Information Security emerges. This branch of Computational Knowledge is concerned with providing data security through network security, software and hardware security, using a wide range of tools and techniques for this purpose. Among these tools and techniques is the use of Kali Linux, a distribution of the Linux operating system specifically developed for Information Security, with tools for penetration testing, detection of various vulnerabilities, and network traffic monitoring. Therefore, the topic of this work is: "Kali Linux: theoretical analysis of its application in information security". Its overall objective was to understand the techniques and tools of Kali Linux for Information Security, through an exploratory research based on a literature review. One of the main final considerations of this work is the efficiency of Kali Linux as a tool for Information Security.